The Transformation of Historical Research in the Digital Age - Milligan, Ian (Cambridge University Press, 2022)
Almost all aspects of the historian's research workflow have been transformed by digital technology. The Transformation of Historical Research in the Digital Age equips historians to be self-conscious practitioners by making these shifts explicit and exploring their long-term impact. This title is also available as Open Access on Cambridge Core.